An Overview on Tall Buildings from The Point of Structural Engineering - Yüksel, İsa (Bursa Teknik Üniversitesi, 2019)
Tall building construction has increased rapidly in Turkey especially in metropolitans such as Istanbul, Ankara, and Bursa. These buildings are subjected to different kinds of loads during its construction and service life time. Substantial load types affecting to tall buildings are gravity loads, seismic and wind loads, and other special loads. Modern lightweight and high strength materials, new force resisting structural systems, shock absorption systems, structuring combinations reveals different solutions to engineers and architects for design and constructing tall buildings. The aim of this paper is to review structural form, wind and earthquake loads on tall buildings from the point of structural engineering. At first, the effect of building form to building aerodynamics is examined. Then the loads, selection and arrangement of the major structural elements to resist loading combinations containing gravity, earthquake, and wind loads on tall buildings are discussed. In addition, the new provisions are reviewed that given in TBEC-2018, which is the first national code comprised special regulations for tall buildings in Turkey.
Keywords: Engineering; Mühendislik